TOPOGRAPHY OF THE CRUST-MANTLE BOUNDARY BENEATH THE BLACK SEA BASIN - Starostenko V.; Buryanov V.; Makarenko I.; Rusakov O.; Legostaeva O.; Stephenson R.; Nikishin A.; Georgiev G.; Gerasimov M.; Dimitriu R.; Sava C.; Pchelarov V. (My University, 2004)
A map of Moho depth for the Black Sea and its immediate surroundings has been inferred from 3-D gravity modelling, and crustal structure has been clarified. Beneath the basin centre, the thickness of the crystalline layer is similar to that of the oceanic crust. In the Western and Eastern Black Sea basins, the Moho shallows to 19 and 22 km, respectively. Below the Tuapse Trough (northeastern margin, adjacent to the Caucasus orogen), the base of the crust is at 28 km, whereas in the Sorokin Trough, it is as deep as 34 km. The base of the crust lies at 29 and 33 km depths respectively below the southern and northern parts of the Mid-Black Sea Ridge. For the Shatsky Ridge (between the Tuapse Trough and the Eastern Black Sea Basin), the Moho plunges from the northwest (33 km) to the southeast (40 km). The Arkhangelsky Ridge (south of the Eastern Black Sea Basin) is characterised by a Moho depth of 32 km. The crust beneath these ridges is of continental type.
Keywords: Black Sea; 3-D gravity modelling; Depth to Moho; Crustal structure; Geodynamics